Identification and molecular analysis of antimicrobial resistant Salmonella isolates obtained from pigs slaughtered at Wambizzi abattoir in Uganda - Tinega, G.M. (Jomo Kenyatta University of Agriculture and Technology, 2015)
Non-typhoidal salmonellosis remains an important public health problem worldwide accounting for an estimated 3 million deaths per year. An economic loss of $2.4 billion has been reported in the USA. The emergence of antimicrobial resistance bacteria in both medical and agricultural fields continues to be a serious problem worldwide. Estimates of salmonellosis due to consumption of pork or pork products is difficult to determine but, it ranges from < 1% to 25%. These invasive pathogens colonize intestinal mucosal surface but, they are self-limiting in health individuals due to a noble immunity. This project examined 54 isolates for antimicrobial resistance, sequenced seven housekeeping genes and performed Multi-Locus Sequence Type (MLST) analysis. β-lactamase and tetB(B) genes were detected in 100% and 80% of the isolates respectively. Widespread inter-isolate sequence type (ST) diversity was revealed thereby showing that the sequences types obtained by MLST analysis were genetically divergent. Codon-based Test of Neutrality analysis between sequences revealed P-value less than 0.05, an indication of strong forces of natural selection pressure acting at the sequence type level. The Maximum Composite Likelihood Estimate of the Pattern of Nucleotide Substitution discovered frequencies of 0.177 (A), 0.244 (T/U), 0.263 (C), and 0.317 (G). The transition/transversion rate ratios were found to be k1 = 2.698 (purines) and k2 = 20.089 (pyrimidines) with and overall transition/transversion bias of R = 6.565, where R = [A*G*k1 + T*C*k2]/[(A+G)*(T+C)] further confirming that indeed the Salmonella isolates studied here were divergent. These results suggest that, STs coexist in the intestine thereby providing for an efficient intestinal colonization and multiple adaptations. The results also offer general and rapid approaches for identifying genetic diversity of Salmonella serotypes in individual pig carcasses which can be adopted for molecular epidemiological surveys of important food contaminating bacterial pathogens. Based on these results, it will be important to carry out a similar study in Kenya in order to evaluate food safety issues related to consumption of animal source foods particularly pigs. In addition it will be important to initiate a study to identify Single Nucleotide Polymorphisms (SNPs) and consequently contribute to the establishment of a Kenyan bioinformatics database.